Brainstem correlates of behavioral and compositional preferences of musical harmony - Bidelman, Gavin M. (2011)
Certain chords are preferred by listeners behaviorally and also occur with higher regularity in musical composition. Event-related potentials index the perceived consonance (i.e., pleasantness) of musical pitch relationships providing a cortical neural correlate for such behavioral preferences. Here, we demonstrate correlates of these harmonic preferences exist at subcortical stages of audition. Brainstem frequency-following responses (FFRs) were measured in response to four prototypical musical triads. Pitch salience computed from FFRs correctly predicted the ordering of triadic harmony stipulated by music theory (i.e., major > minor ≫ diminished > augmented). Moreover, neural response magnitudes showed high correspondence with listeners’ perceptual ratings of the same chords. Results suggest that pre-attentive stages of pitch processing may contribute to perceptual judgments of musical harmony.